Bhārata kā mukti saṅgharsha aura Rūsī Krānti, 1930-1947 - Upādhyāya, Viśvamitra, 1933- (Navayuga Pabliśarsa, 1982)
India-Soviet relations, 1930-1947; a study in the light of the impact of the Bolshevik Revolution on the Indian Independence struggle.